Flagellates as model system for gravity detection of single cells - Lebert, Michael; Richter, Peter; Daiker, Viktor; Schuster, Martin; Tebart, Jennifer; Strauch, Sebastian; Häder, Donat-Peter (38th COSPAR Scientific Assembly, 2010)
Euglena gracilis is a unicellular, photosynthetic organism which uses light and gravity as en-vironmental hints to reach and stay in horizons of the water column which are optimal for growth and reproduction. The orientation in respect to light (so called positive and nega-tive phototaxis, i.e. movement toward or away of a light source) was well known and fairly good understood. In contrast, knowledge about the movement away from the centre of gravity (negative gravitaxis) was rather scarce. Over a century it was unclear whether orientation in respect to the gravity vector is based on a physical or a physiological mechanism. Recent results clearly favour the latter. Knock-down mutants (RNAi) were characterized which define certain key components of the gravitactic signal transduction chain. These key components include a TRP-like channel, a gravitaxis-specific calmodulin and a protein kinase A. The molecular characterization of these components is currently performed and will be presented. Euglena is not only a model system for the close understanding of gravity detection in single cells, but can also be used as photosynthetic component, i.e. oxygen source and carbon dioxide as well as nitrogenic components sink in Closed Environmental Systems (CES). Due CES are systems of choice in times of scarce flight opportunities. They allow a massive sample sharing and combine possibilities to do microgravity research for biologists but also for engineers, physicists and material scientists. Recent attempts include Aquacells and Omegahab. In the near future miniaturized systems (Chinese ShenZhou) as well as advanced CES will be flown or tested, respectively. Current attempts and plans will be presented.